2015
DOI: 10.1007/s12282-015-0583-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aldehyde dehydrogenase 1 and transcription factors in both primary breast cancer and axillary lymph node metastases as a prognostic factor

Abstract: The evaluation of the co-expression of ALDH1 and transcription factors in primary lesions may be useful in prognosis of node-positive breast cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…CSCs may be responsible for the resistance of chemotherapy, which leads to relapse and multidrug resistance in cancer disease . Currently, the evaluation of CD44, CD24 and ALDH1 expressions is considered as the most precise methodology to identify CSCs in the breast cancer women . Recently, both CD24 and CD44 have been proven as good CSCs markers in chemocarcinogen‐induced rat mammary tumorigenesis .…”
Section: Discussionmentioning
confidence: 99%
“…CSCs may be responsible for the resistance of chemotherapy, which leads to relapse and multidrug resistance in cancer disease . Currently, the evaluation of CD44, CD24 and ALDH1 expressions is considered as the most precise methodology to identify CSCs in the breast cancer women . Recently, both CD24 and CD44 have been proven as good CSCs markers in chemocarcinogen‐induced rat mammary tumorigenesis .…”
Section: Discussionmentioning
confidence: 99%
“…For example, TWIST1 expression is associated with poor prognosis in patients with ER+ breast cancer41 and primary breast cancer42. The Zhang P. et al .…”
Section: Discussionmentioning
confidence: 99%
“…Among the included articles, the protein expression level was detected using IHC in 22 studies [6,8,10,12,13,[15][16][17][18][19][20]25,[29][30][31][32][33][34][35][36][37][38], the mRNA transcriptional level was probed by RT-qPCR in 5 studies [7,9,14,22,39], and both methods were used in 1 study [10]. In terms of the NOS scale, 9 articles scored 9, 4 articles scored 8, 7 articles scored 7 and 3 articles scored 6 in the protein group; 2 articles scored 9, 2 articles scored 8 and the rest two articles scored 7 and 6, respectively, in the mRNA group ( Table S1).…”
Section: Studies Identification and Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Slug (Snail2) is a zinc finger protein of the Snail family, which was first found in the neural crest and developed into mesoderm of early chick embryos [5]. Its expression has been investigated in different types of cancers, such as oesophageal carcinoma [6,7], gastric carcinoma [8,9], colorectal carcinoma [10,11], hepatocellular carcinoma [12], pulmonary carcinoma [13][14][15][16], head and neck squamous cell carcinoma (HNSCC) [13,14], breast cancer [15][16][17], prostate cancer [18], bladder cancer [19,20], gynaecological cancer [21,22] and malignant mesothelioma [23]. Some studies have demonstrated slug expression was related to tumour aggressiveness, as was confirmed by the association with tumour grade, distant metastasis and shorter survival of patients, no matter whether there was loss of E-cadherin expression [24].…”
Section: Introductionmentioning
confidence: 99%